Frequency of C-Shaped Root Canals in Permanent Mandibular Second Molars in a Sample of Pakistani Population using Cone Beam Computed Tomography: Frequency of C-Shaped Root Canals - Ahmed, Syed Nabeel; Majeed, Muhammad Mansoor; Kazmi, Sakina; Ansari, Muhammad Omar (Pakistan Journal of Health Sciences, 2024)
C-shaped root tubes have a challenging design that causes issues in the clinic. Endodontic therapy requires careful consideration of the C-shape root canal design in Pakistan due to the country’s high carious rate (about 60%). Objective: To determine the frequency of C-shaped root canals in permanent mandible second molars among Pakistani adults. Methods: At Karachi’s Altamash Dental Hospital, cross-sectional study was conducted between March 2021 and January 2022.We used mandibular CBCT images to analyze 302-second molars. The position of the longitudinal groove and the bilateral predominance of C-shaped root canals were also observed. A chi-square test was used for the statistical analysis. Results: 47 teeth (15.54%) out of 302 had a “C-shaped canal” configuration. The breakdown was as follows: 31.91% in Category 1 (C1), 14.89% in Category 2 (C2), 6.38% in Category 4 (C4), and 46.80% in Category 3 (C3). There was no appreciable variation in the prevalence of C-shaped canals between the genders; 32.14% of the patients had them unilaterally and 67.85% had them bilaterally. Conclusions: “C-shaped canals are found in 15.54% of the mandibular second molars” in the Pakistani sample group, and a high probability of a matching lingual groove (59.57%) is present in these teeth. The most common type of C-shaped root canals observed in this study is C3.